Pengaruh Kemampuan Penyusunan Laporan Keuangan, Kompetensi UMKM dan Latar belakang pendidikan terhadap Kinerja UMKM - Winarso, Beni Suhendra; Kurniawati, Indah Kurniawati (Program Studi Manajemen, 2022)
The objectives this study to analyze the influence of the ability of financial report preparation, educational background, and competence of MSMEs on the operational performance of MSMEs. The study population was MSMEs in the Special Region of Yogyakarta with a sampling technique using a questionnaire distributed during the Covid-19 pandemic with the criteria for MSMEs that had been standing for at least three months. This research method uses multiple regression models. The statistical analysis conducted was validity test, reliability test, residual data normality test using one sample Kolmogorof Smirnof, multicollinearity test, heteroscedastic test, t test, and determination coefficient test. The test results show that the ability to compile financial reports and the competence of MSMEs has a positive effect on the performance of MSMEs, while the educational background of MSMEs does not have a positive effect on the performance of MSMEs.